Employee Performance and Retention: The Role of Supervisor Support and Work Motivation at Five Star Hotels in Bali - Astawa, I Ketut; Suardani, Anak Agung Putri; Armoni, Ni Luh Eka (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: The problems raised in this study are the effect of supervisor support on employee work motivation, the effect of work motivation on employee performance, and the effect of work motivation on employee retention at 5-star hotels in Bali. This study aims to analyze the importance of supervisor support in motivating operational employees and its implications for work performance and employee retention in 5-star hotels in Bali. Research methods: The population in this study is all permanent employees at 5-star hotels in Bali. The number of research respondent samples of 125 was determined by purposive sampling. The research data used are primary data and secondary data. The data processing method is carried out with SEM with SmartPLS 4. Results and discussion: The effect of supervisor support on employee work motivation at a 5-star hotel in Bali 64.9% was positive and significant, which means that the higher the supervisor support, the higher the employee's work motivation. Employee work motivation has a positive and significant effect of 64.6% on employee performance, and work motivation affects employee retention positively and significantly by 52.5%. After considering the control variable, the increased R-Square value suggests that supervisor support positively impacts employee motivation if employees have a high education. Implication: Aspects of educational level greatly influence a supervisor in making decisions to motivate employees at a 5-star hotel in Bali. Decision-making is faster and more structured because it has a mature theoretical foundation. The higher the education, the more comprehensive the supervisor's insight. A supervisor with an unmarried status has speed in making decisions and motivates his employees. From a gender perspective, women cannot freely determine workload and work shifts compared to men.